The Contribution of Teacher Work Motivation and School Climate to Work Achievement - Bestari, Putri; Hadiyanto; Gistituati, Nurhizrah; Alkadri, Hanif (Universitas Jambi, Indonesia, 2024)
The research’s objective is to explore the contribution of teacher work motivation and school climate to teacher work achievement at the public elementary school, IV Jurai District, Pesisir Selatan Regency, by using a correlational quantitative approach with an ex post facto type of research. This research covers a teacher population of 225 people. The sample size was determined using the Cochran formula, and stratified proportional random sampling resulted in a sample of 102 teachers being selected based on class and length of service. Likert Scale Questionnaire, validated and reliable, facilitates data collection. The research results revealed (1) the contribution of teacher work motivation to teacher work achievement, (2) the contribution of school climate to teacher work achievement, (3) the contribution of teacher work motivation and school climate to teacher work achievement at the public elementary school, IV Jurai District, Pesisir Selatan Regency.